2021
DOI: 10.3390/ijms22179291
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellins Inhibit Flavonoid Biosynthesis and Promote Nitrogen Metabolism in Medicago truncatula

Abstract: Bioactive gibberellic acids (GAs) are diterpenoid plant hormones that are biosynthesized through complex pathways and control various aspects of growth and development. Although GA biosynthesis has been intensively studied, the downstream metabolic pathways regulated by GAs have remained largely unexplored. We investigated Tnt1 retrotransposon insertion mutant lines of Medicago truncatula with a dwarf phenotype by forward and reverse genetics screening and phylogenetic, molecular, biochemical, proteomic and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 96 publications
(124 reference statements)
2
9
0
Order By: Relevance
“…Moreover, studies also showed that the GA-DELLA module is involved in nitrogen-deficiency-induced anthocyanin accumulation. DELLAs could interact with PAP1 and enhance the transcriptional activity of PAP1 to promote the expressions of F3 H and DFR [37,101].…”
Section: Nutrient-limitation-induced Anthocyanin Accumulation In Plantsmentioning
confidence: 99%
“…Moreover, studies also showed that the GA-DELLA module is involved in nitrogen-deficiency-induced anthocyanin accumulation. DELLAs could interact with PAP1 and enhance the transcriptional activity of PAP1 to promote the expressions of F3 H and DFR [37,101].…”
Section: Nutrient-limitation-induced Anthocyanin Accumulation In Plantsmentioning
confidence: 99%
“…Treatment with ABA results in a higher accumulation of total anthocyanin via increasing the expression of VvCHI and VvF3H in grape (Koyama et al., 2018). In Medicago truncatula , GA inhibits the biosynthesis of flavonoid and isoflavonoid via regulating the transcripts of flavonoid biosynthesis genes, such as MtCHI , MtCHS , and MtDFR (Sun et al., 2021). Future work needs to unravel the mechanism by which ABA and GA affect the age‐related flavonoid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous GA is extremely important when encountering biotic or abiotic stress. Endogenous GA reduction might increase flavonoid content in plants [ 46 ] and contribute to improving plant ability to resist stress [ 47 ]. Therefore, the chlorophyll and leaf nitrogen increasing due to PAC application might affect plant resistance to abiotic or biotic stress.…”
Section: Discussionmentioning
confidence: 99%